Analysis of nuclear safety in diversification of Westinghouse fuel assemblies at WWER-1000 - V. I. Skalozubov; I. L. Kozlov; Yu. A. Komarov; O. A. Chulkin; O. I. Piontkovskyi (Ядерна фізика та енергетика)
The research presents an analysis of the known results in modeling the maximum design accident (MDA) using the code RELAP5/V3.2 with Westinghouse fuel assemblies’ (WFA) diversification in WWER-1000 reactors. According to the known results of MDA calculated model simulation with RELAP5/V3.2 code at the maximum allowable water temperature in the heat WWER emergency cooling system exchanger (90 °С), the fuel elements’ claddings temperature reaches 1320 °С and exceeds the admissible nuclear safety limit (1200 °С). Thus, according to known results, these MDA with WFA engaged pass from the "design" accident status to the "severe" accident status and means a decrease in safety in relation to the FA-A fuel assemblies. The alternative MDA analysis for WFA-equipped plants showed that, unlike the known calculations, the nuclear safety limit on the maximum permissible fuel cladding temperature is not violated and never reduces the overall safety level in WWER diversification with WFA fuel assemblies.